Ocorrência de tritrichomonas foetus em gatos na região do município de Araçatuba - SP, Brasil - Duarte, Roberta Picciuto [UNESP] (2015)
The present study investigated the occurrence of T. foetus in cats from Brazil. T. foetus is a protozoan that in cats it colonizes the colon resulting in colitis. The major clinical sign is chronic large bowel diarrhea. Infected cats may have spontaneous resolution of diarrhea, but they can remain infected for all life. In veterinary medical practice, there are three most widespread diagnostic methods that identify T. foetus in animal feces: direct examination of feces under the microscope, culture and PCR. In the present study, it was compared two diagnosis methods, direct examination of feces and PCR. And also it was done the genetic sequencing. Fecal samples from 129 cats were collected by rectal flush technique. Each sample was examined by optical microscopy (direct examination). The presence of T. foetus DNA was verified using PCR by amplification of 347 bases pairs from the primers TFR3 and TFR4. Amplicons of positive cases were sequenced. T. foetus was observed in one sample by direct microscopic examination of feces while PCR was positive in five cats (6.45%). Statistical analyses showed no significant associations between T. foetus infection and sex, age, breed, presence of diarrhea, history of diarrhea, previous treatment, lifestyle, environment, origin of the animals, and co-infections. The isolate of T. foetus showed 100% identical sequences with other T. foetus isolates from cats around the world and revealed a single nucleotide polymorphism (T>C) when compared with T. foetus isolate from cattle. Due the increasing interest in this parasite in cats, the present study contributes in further reporting the worldwide occurrence of T. foetus in cats because it is the first study about its occurrence in Brazil.